The experience of democracy and bureaucracy in South Korea - Im, To-bin (Emerald Publishing Limited, 2017)
South Korea is renowned as one of the success stories of fast economic development. The Korean developmental state was a highly efficient, meritocratic, and fully monopolized coercive force. These resources were skilfully leveraged to shape the direction of private sector actors towards strategic initiatives. However, these very same resources could have resulted in the bureaucracy retaining its power indefinitely. Instead, step-by-step, the resources of the bureaucracy, which serviced the authoritarian leadership in the developmental period, were exercised towards democratization. What were the conditions that made this transformation possible? The Experience of Democracy and Bureaucracy in South Korea addresses this question, filling the existing gap in the academic literature and presenting political implications. It explores the ways in which bureaucracy may not only be compatible with democracy but, more ambitiously, the conditions under which it can enhance it. The chapters examine the unique systems and institutions of the Korean bureaucracy including the National Election Commission, the police force, local government, the ceiling recruitment strategy, and procurement policy. This timely collection will be of interest to researchers, graduate and undergraduate students in public administration and policy. It will also be a useful reference for bureaucrats in developing countries who seek to design policy for bureaucracy in concurrence with democratization.- Resumé vydavatel
Obsahuje index.
Keywords: byrokracie -- Korejská republika; demokracie -- Korejská republika; ekonomický růst -- Korejská republika; demokratizace -- Korejská republika; bureaucracy -- Korea (South); democracy -- Korea (South); economic development -- Korea (South); democratization -- Korea (South); Korejská republika -- politika a vláda; Korea (South) -- politics and government; sborníky; elektronické knihy; papers of several authors; electronic books